Slavs and Tatars and the Performative Proposal for Polish Comparative Culture Studies - Iwanczewska, Łucja (Porównania, 2020)
The article is a view of Polish comparative culture studies through the prism of performance science understood as the study of performative processes of establishments. The author shows that performance can become a proposal for comparative methodologies. By analyzing the strategies of the artistic and scientific collective Slavs and Tatars, she shows how knowledge and history are produced in a performative way, how dependencies and relationships between disciplines of knowledge and cultural texts are created.